β3 subunit of Na,K ATPase regulates T cell activation with no involvement of Na,K ATPase activity - Nuttapol Chruewkamlow (2018)
© 2015 Elsevier GmbH. Na,K ATPase plays an important role in the regulation of Na + and K + ions that are required for normal resting membrane potential and various cellular functions. Na,K ATPase is composed of two subunits, α and β subunits. Engagement of the β subunit by an agonistic monoclonal antibody (mAb) P-3E10 inhibited T cell activation and induced the G0/G1 cell cycle arrest. In addition, mAb P-3E10 decreased CD25 expression. The mAb P-3E10, however, did not inhibit the proliferation of cell lines and the phagocytosis activity of phagocytes, and did not interfere with the Na,K ATPase activity. These results indicate that mAb P-3E10 reacts to the β subunit and, as a consequence, brings about the regulation of the T cell activation without disturbing the Na,K pump activity. By sequential immunoprecipitation, we demonstrated the expression of the β3 subunit free form apart from the α subunit. In this study, we propose that the β3 subunits of Na,K ATPase are expressed separately from the α subunit, and play a role in regulation of the immune response.